Metallothionein 3 Expression in Normal Skin and Malignant Skin Lesions - Pula, Bartosz (Pathol Oncol Res, 2014)
Metallothionein-3 (MT-3) has been shown to be expressed in several malignancies and to have an impact on patients’ survival in breast and urinary bladder cancer cases. However, its expression has not been determined in normal skin or in its malignant lesions. MT-3 expression was studied using immunohistochemistry in 17 cases of normal skin, 18 of actinic keratosis (AK), 39 of squamous cell carcinoma (SCC), and 23 of basal cell carcinoma (BCC). Low MT-3 expression was observed in normal skin epidermis with faint or no expression in the epidermis basal layer. Significantly higher MT-3 expression was noted in AK (P = 0.007) and SCC (P < 0.0001), as compared with normal skin epidermis. BCC cases were characterized by the lowest MT-3 expression of all the examined groups, which was significantly lower in comparison to normal skin epidermis, AK, and SCC (P = 0.009; P < 0.0001 and P < 0.0001, respectively). In conclusion, MT-3 may be involved in the development of SCC.